The college transition experience of students with ADHD - Morgan, Kristy (Kansas State University, 2012)
This qualitative study explored the college transition experience of eight first-year students with Attention Deficit Hyperactivity Disorder at a midwestern research university. Using a three-interview-series model, students participated in structured interviews designed to explore their backgrounds, discuss their current experiences on campus, and discover what they have learned from their college transition experiences. The findings reveal that these students with ADHD did not adequately plan their college transitions, relied heavily on family for assistance with their transition and medical treatment, did not utilize many campus resources available to them, and lacked strategies to manage their ADHD symptoms. Additionally, they found the process of becoming college students to be stressful due to the many responsibilities inherent in the role. Findings also indicate that students relied on medication to perform academically in college; however, they lacked knowledge of medication and treatment options. The results contribute to research addressing individuals with ADHD across the lifespan, particularly in college, as well as research of college students and college environments. Recommendations for practice and future research are discussed.
Keywords: ADHD; College student; Transition; Qualitative; First year; University; Educational Administration (0514)